2022
DOI: 10.1080/00036846.2022.2041176
|View full text |Cite
|
Sign up to set email alerts
|

Subsidies to microfinance institutions: how do they affect cost efficiency and mission drift?

Abstract: The costs and benefits of subsidized microfinance are still controversial. We utilize a costfunction estimation approach that accounts for the double bottom line (social and financial) of microfinance institutions (MFIs) to evaluate how subsidies affect both cost efficiency and risk of mission drift. We control for endogenous self-selection into the business models of credit-only versus credit-plus-deposit. Our results suggest that MFIs that both supply loans and collect deposits need no subsidies to be cost-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…Mia et al (2022) found that more leveraged MFIs had lower cost while the number of leverage sources (donations and loans to the MFI) did not affect costs, suggesting a role for deposits because of their effect on leverage. This result is consistent with recent literature on MFI efficiency and scope economies highlighting the need to account for business type (Malikov & Hartarska, 2018) and the findings that savings and subsidies interfere to affect scale economies in saving‐and‐loan MFIs (Cozarenco et al, 2022). Dasgupta and Roy Chowdhury (2022) show a different mechanism for efficiency differences by MFIs business type.…”
Section: Brief Literature Overviewsupporting
confidence: 92%
See 3 more Smart Citations
“…Mia et al (2022) found that more leveraged MFIs had lower cost while the number of leverage sources (donations and loans to the MFI) did not affect costs, suggesting a role for deposits because of their effect on leverage. This result is consistent with recent literature on MFI efficiency and scope economies highlighting the need to account for business type (Malikov & Hartarska, 2018) and the findings that savings and subsidies interfere to affect scale economies in saving‐and‐loan MFIs (Cozarenco et al, 2022). Dasgupta and Roy Chowdhury (2022) show a different mechanism for efficiency differences by MFIs business type.…”
Section: Brief Literature Overviewsupporting
confidence: 92%
“…We specify a cost function following the relevant banking and microfinance literature and apply a modification that accounts for the limited number of rural‐only observations and the specific nature of our data. Specifically, we use the translog functional form adapted from the banking literature (Gilligan et al, 1984; Hughes & Mester, 2013) and the microfinance literature (e.g., Caudill et al, 2009; Cozarenco et al, 2022; Malikov & Hartarska, 2018). The cost function is: lnCnewline=β0goodbreak+iβilnyigoodbreak+12ijβijlnyilnyjgoodbreak+nγnlnwngoodbreak+12nmγnmlnwnlnwmgoodbreak+1emniδnilnwnlnyigoodbreak+φ1lnrgoodbreak+φ2lnr2goodbreak+iθilnrlnyigoodbreak+nρnlnrlnwngoodbreak+λ1lnegoodbreak+1emλ2lne2goodbreak+iνilnelnyigoodbreak+nτnlnelnwngoodbreak+κlnrlnegoodbreak+ψ1tgoodbreak+ψ2t2goodbreak+iαitlnyigoodbreak+1emnϕntlnwngoodbreak+italicζtlnrgo...…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some segments of social banking, such as microcredit activities benefit however from a specific regulatory framework that recognizes their prosocial specifies. Regulators in most industrialized countries carefully monitor the activities of microcredit institutions, probably because these institutions receive significant subsidies from national and supranational public authorities and their activities belong to social finance (Morduch and Ogden, 2019;Cozarenco et al, 2022). Key regulatory rules impose ceilings on interest rates and loan sizes (see Cozarenco and Szafarz, 2019, for a detailed lists of obligatory and recommended ceilings in place in North America and Europe).…”
Section: Discussionmentioning
confidence: 99%